First record of the foraminiferal genera Clypeorbis Douvillé and Ilgazina Erdoğan from the Maastrichtian of the Arabian Peninsula (Simsima Formation, North Oman): Paleobiogeographic implications. (October 2022) - Özcan, Ercan; Abbasi, İftikhar Ahmed; Yücel, Ali Osman; Aşcı, Serhat Yiğit; Erkızan, Levent Sina; El-Ghali, Mohamed A.K.; Çalışkan, Dilay; Gültekin, Münire Nur; Kayğılı, Sibel
Abstract: The Maastrichtian orbitoidiform foraminiferal genera Clypeorbis Douvillé, previously reported as endemic to the 'European Faunal Province' and Ilgazina Erdoğan, as yet only known from Turkey with poor illustrations, co-occur in the transgressive beds of the Simsima Formation in north Oman. The present records of these complex genera and their species C. mamillatus (Schlumberger) and I. unilateralis Erdoğan from the southern part of the Arabian Peninsula ('African Faunal Province'), enable us to re-evaluate their biogeographic affinities. In addition, due to the incomplete original description, the diagnosis of I. unilateralis, which looks like a 'broken- Orbitoides in half' with a single layer of lateral chamberlets, is revised and emended by describing the megalospheric embryon and other test features for the first time. The embryonic apparatus of this species differs from that of the closely associated genus Orbitoides d'Orbigny by having an 'Y'-shaped trilocular embryon with only two principal epi-embryonic chamberlets arising from it. In addition, the hyaline lateral layer without chamberlets presents compressed 'vacuolar' structures that are comparable with the canals in the Paleocene genus Lakadongia Matsumaru and Jauhri, endemic to the Indian Subcontinent. Because of these morphological features Ilgazina differs significantly from other Late Cretaceous orbitoidiform taxa. A Maastrichtian age (but not the latest) is indicated for the Simsima Formation based on assemblages of Lepidorbitoides with transitional developmental stage between L. minor (Schlumberger) and L. socialis (Leymerie), Orbitoides gensacicus (Leymerie), O. ' medius ' (d'Archiac), Omphalocyclus macroporus (Lamarck), Siderolites gr. calcitrapoides Lamarck, Sirtina orbitoidiformis Brönnimann and Wirz, Planorbulina cretae (Marsson) and Goupillaudina Marie. Highlights: The Maastrichtian Simsima Formation contains Ilgazina and Clypeorbis, reported for the first time from the Arabian Peninsula. Paleogeographic distributions of Ilgazina and Clypeorbis are reevaluated. An emended diagnosis of the poorly known genus Ilgazina is given. The larger benthic foraminifera of the Simsima Formation are briefly illustrated and discussed.